Synthesis and Structural Characterization of N-(2-Carboxyphenyl)-exo-7-oxa-bicyclo[2,2,1]hept-5-ene-2,3-dicarboximide - Zhu, Xiao-Yu; Liang, Zu-Pei; Li, Jian; Gao, Jun; Zhang, Zhi-Shan (Asian Journal of Chemistry, 2013)
The compound N-(2-carboxyphenyl)-exo-7-oxa-bicyclo[2,2,1]hept-5-ene-2,3-dicarboximide (C15H11NO5, Mr = 285.25) was synthesized and characterized by elemental analysis, 1H NMR spectra, IR spectra and single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/n, with a = 8.4994(8), b = 14.6499(15), c = 10.2880(10) Å, b = 101.5890(10)º, V = 1254.9(2) Å3, Z = 4, Dc = 1.510 g/cm3, l = 0.71073 Å, (MoKa) = 0.115 mm-1, F(000) = 592. The final refinement gave R = 0.0374, wR(F2) = 0.0856 for 2,201 observed reflections with I > 2s(I). The structure of the compound comprises a racemic mixture of chiral molecules containing four stereogenic centres. X-Ray diffraction analysis reveals that the cyclohexane ring tends towards a boat conformation, the tetrahydrofuran ring and the dihydrofuran ring adopt envelope conformations. The dihedral angle between the pyrrolidine-2,5-dione plane and the aromatic ring is 65.0 (1)º. The crystal structure is stabilized by O-H···O and C-H···O hydrogen bonds.